2018
DOI: 10.1186/s12889-018-6043-z
|View full text |Cite
|
Sign up to set email alerts
|

Water insecurity and gendered risk for depression in rural Uganda: a hotspot analysis

Abstract: BackgroundWater insecurity is linked to depression in low- and middle-income countries (LMICs), though it remains unclear how geospatial clustering of water insecurity in rural regions is associated with risk for depression.MethodsWe conducted a population-based survey of a rural parish in southwestern Uganda (N = 1603) to evaluate the joint geospatial clustering of water insecurity and risk for depression among men and women living in rural Uganda.ResultsGeospatial clustering of self-reported water insecurity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 62 publications
4
44
0
Order By: Relevance
“…That stress can be related to uncertainty as to when water will become available, stigma or shame due to unmet social expectations (eg, for hygiene), or perceived injustices and inequities in how safe water is distributed (Wutich & Brewis, ). Water‐related distress appears to worsen common mental health disorders, such as anxiety and depression (Aihara, Shrestha, & Sharma, ; Cooper‐Vince et al, ; Stevenson et al, ; Subbaraman et al, ; Workman & Ureksoy, ; Wutich, Brewis, Chavez, & Jaiswal, ). Low water access has also recently been linked to physical manifestations of stress as well, such as heightened blood pressure (Brewis, Choudhary, & Wutich, , ).…”
Section: Why Assess Water Needs?mentioning
confidence: 99%
“…That stress can be related to uncertainty as to when water will become available, stigma or shame due to unmet social expectations (eg, for hygiene), or perceived injustices and inequities in how safe water is distributed (Wutich & Brewis, ). Water‐related distress appears to worsen common mental health disorders, such as anxiety and depression (Aihara, Shrestha, & Sharma, ; Cooper‐Vince et al, ; Stevenson et al, ; Subbaraman et al, ; Workman & Ureksoy, ; Wutich, Brewis, Chavez, & Jaiswal, ). Low water access has also recently been linked to physical manifestations of stress as well, such as heightened blood pressure (Brewis, Choudhary, & Wutich, , ).…”
Section: Why Assess Water Needs?mentioning
confidence: 99%
“…Water insecurity leads to emotional stress, anger, anxiety, shame and stigma, social exclusion, and threatens mental health particularly among women (Bisung & Elliott, ; Hadley & Wutich, ; Tutu & Stoler, ; Wutich & Ragsdale, ). The psychosocial effects of water insecurity are gendered, with women bearing a disproportionately higher burden (Cooper‐Vince et al, ; Stevenson et al, ). In Ethiopia, women who were water insecure were more likely to report mental health disorders (Stevenson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Water insecurity is definitely associated with psychosocial distress and other negative mental health outcomes. This has been demonstrated by scholars using a range of methods around the world, including Ennis‐McMillan () in Mexico, Sultana () in Bangladesh, Aihara et al (); Aihara, Shrestha, and Sharma () in Nepal, in Kenya by Bisung and Elliott (, ) and Young's group (Collins et al, ; Krumdieck et al, ), Bulled () in South Africa, and Tsai's group (Cooper‐Vince et al, ) in Uganda.…”
Section: Recent Research On Water Insecurity and Distressmentioning
confidence: 92%
“…Importantly, some of this newer work has shown that water insecurity is associated with symptoms of common mental disorders, as measured by validated screeners for symptoms of common mental disorders such as anxiety and depression (Aihara et al, ; Cooper‐Vince et al, ; Stevenson et al, ; Subbaraman et al, ; Workman & Ureksoy, ). In our own work in Bolivia, we found in a study of women from 28 informal communities that water insecurity was not just associated with emotional distress; it was also associated with symptoms of common mental disorders like anxiety and depression as measured by the Standard Reporting Questionnaire and Hopkins Symptom Checklist (Wutich, Brewis, et al, ).…”
Section: Recent Research On Water Insecurity and Distressmentioning
confidence: 99%